Investigations of Heavy Metal Ion Sorption Using Nanocomposites of Iron-Modified Biochar - Kołodyńska, D. (Nanoscale Res Lett, 2017)
Magnetic biochar nanocomposites were obtained by modification of biochar by zero-valent iron. The article provides information on the impact of contact time, initial Cd(II), Co(II), Zn(II), and Pb(II) ion concentrations, dose of the sorbents, solution pH and temperature on the adsorption capacity. On the basis of experiments, it was found that the optimum parameters for the sorption process are phase contact time 360 min (after this time, the equilibrium of all concentrations is reached), the dose of sorbent equal to 5 g/dm(3), pH 5 and the temperature 295 K. The values of parameters calculated from the kinetic models and isotherms present the best match to the pseudo second order and Langmuir isotherm models. The calculated thermodynamic parameters ∆H (0), ∆S (0) and ∆G (0) indicate that the sorption of heavy metal ions is an exothermic and spontaneous process as well as favoured at lower temperatures, suggesting the physical character of sorption. The solution of nitric acid(V) at the concentration 0.1 mol/dm(3) was the best acidic desorbing agent used for regeneration of metal-loaded magnetic sorbents. The physicochemical properties of synthesized composites were characterized by FTIR, SEM, XRD, XPS and TG analyses. The point characteristics of the double layer for biochar pH(PZC) and pH(IEP) were designated.